2012
DOI: 10.1038/npp.2012.152
|View full text |Cite
|
Sign up to set email alerts
|

Candesartan, an Angiotensin II AT1-Receptor Blocker and PPAR-γ Agonist, Reduces Lesion Volume and Improves Motor and Memory Function After Traumatic Brain Injury in Mice

Abstract: Traumatic brain injury (TBI) results in complex pathological reactions, the initial lesion worsened by secondary inflammation and edema. Angiotensin II (Ang II) is produced in the brain and Ang II receptor type 1 (AT 1 R) overstimulation produces vasoconstriction and inflammation. Ang II receptor blockers (ARBs) are neuroprotective in models of stroke but little is known of their effect when administered in TBI models. We therefore performed controlled cortical impact (CCI) injury on mice to investigate whethe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
107
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 103 publications
(120 citation statements)
references
References 84 publications
8
107
0
Order By: Relevance
“…Mice with mild and severe TBI in this experiment confirmed previous reports [75][76][77][78] of transient impairments in motor coordination as measured on an accelerating rotarod, and here brain-injured males and females had equivalent performance (Fig. 4).…”
Section: Traumatic Brain Injury Equally Impairs Motor Coordination Onsupporting
confidence: 91%
“…Mice with mild and severe TBI in this experiment confirmed previous reports [75][76][77][78] of transient impairments in motor coordination as measured on an accelerating rotarod, and here brain-injured males and females had equivalent performance (Fig. 4).…”
Section: Traumatic Brain Injury Equally Impairs Motor Coordination Onsupporting
confidence: 91%
“…41 We have previously reported that the systemic administration of the ARB, candesartan, reduces cerebral cortical lesion volume and inflammation, and improves motor and cognitive behavior after TBI. 42 We found similar neuroprotective results after TBI with another ARB, telmisartan. 43 Telmisartan, a highly selective AT1R antagonist, has been reported to exert potent systemic antioxidative and anti-inflammatory effects.…”
supporting
confidence: 74%
“…42 Lesion volume was obtained by multiplying the sum of the lesion areas by the distance between sections, with between 9 and 15 brain sections required to bridge the lesion. Percentage lesion volume was calculated by dividing each lesion volume by the total ipsilateral hemisphere volume.…”
Section: Microscopy and Quantitative Analysismentioning
confidence: 99%
“…Inhibition of the RAS with angiotensin-converting enzyme inhibitors (ACE-Is) and angiotensin receptor blockers (ARBs), which selectively block the AT 1 R, are, therefore, widely used for the treatment of hypertension and CVD. There is a growing body of evidence, however, demonstrating that the therapeutic actions of both ACE-Is and ARBs extend beyond blood pressure reduction (11,92,108) and may have beneficial effects on stress-related pathologies, such as PTSD and panic disorder (43,50).…”
Section: The Renin-angiotensin System: Beyond Blood Pressure Controlmentioning
confidence: 99%
“…Inhibition of the RAS with angiotensin-converting enzyme inhibitors (ACE-Is) and angiotensin receptor blockers (ARBs), which selectively block the AT 1 R, are, therefore, widely used for the treatment of hypertension and CVD. There is a growing body of evidence, however, demonstrating that the therapeutic actions of both ACE-Is and ARBs extend beyond blood pressure reduction (11,92,108) and may have beneficial effects on stress-related pathologies, such as PTSD and panic disorder (43,50).Chronic stress, as manifested with PTSD, induces activation of the RAS, leading to increased ANG II synthesis (86). Experimental studies have shown that immobilization stress in rats increases circulating levels of ANG II (18) and binding of brain AT 1 R. Inhibition of the RAS using ACE-Is and ARBs can reverse these affects (6,17,62,94).…”
mentioning
confidence: 99%